Structural style of the eastern flank of the Sira Mountains - Reyes Rivera, Luis Guillermo (2012)
Over a metamorphic intrusive basement, outcrop sedimentaries units that are from Paleozoic age until Cenozoic age; these rocks are deformed by a dominant structural style of wide and long fold of andean direction, related with thrust faults regionals with slope toward Est. In its geological history, it was recognized expansive and compresive tectonics, that have had some influency on lithologic sediments, in the upper and lower structural formations, in the inverted tectonic and in the absence of some stratigraphic units. Likewise it was determined that some stratigraphic units are potencialy hidrocarburiferous source rocks and others with good visual porosity are reservoir rocks. In addition there are some favorable structures to entrap fluids, which mst be confirmed with seismic reflextion.